DISPARITAS FISKAL ANTARDAERAH DI PROVINSI JAWA TENGAH * - Sriyana, Jaka (Universitas Muhammdaiyah Surakarta, 2011)
Local fiscal capacity plays a crucial role in the implementation of regional development. This study aims to examine the fiscal disparities among regions in Central Java province in 2007-2009 period. The research method used is the average difference test against various classes/groups of local fiscal variables, namely level of independence and the degree to fiscal dependency. From the results of the analysis, indicate a significant disparity between the city/county. For the analysis of disparities in fiscal independence, indicate a disparity of high and relatively constant. As for the analysis of disparities in fiscal dependence, indicate a relatively low disparities between city/county. These results imply that the city and district in Central Java province has continued in fiscal independence vary widely but tend to have nearly the same fiscal dependency. This condition will affect the low level of local government discretion in planning and execution of development in the region.